Kinematic and dynamic investigation of a novel inertial propulsion drive - Timofte, Stelica; Korka, Zoltan; Gerocs, Attila; Wisznovszky (Muncut), Elena Stela; Sfetcu, Camelia Rodica (Analecta Technica Szegedinensia, 2022)
Today there is a great deal of controversy over the operation of inertial propulsion drives (IPD), as they challenge the laws of Newtonian mechanics. Starting with the last decades of the previous century, many devices that use the centrifugal force to generate linear propulsion were patented. Regrettably, whether we are talking about the initial, or the most recent attempts, only a few of these systems passed the patent stage and were involved for practical applications. The aim of this paper is to present an IPD, developed by the authors, which uses for generating linear motion the kinetic energy of several masses, placed in the articulation points of the links of a chain drive. The masses placed equidistantly along the half-length of the chain perform a complex movement, consisting of the specific displacement of the chain elements and a rotation around an axis, that is parallel to the line which joins the centres of the chain wheels. After deducting the equations of the geometric coordinates of the masses, the total propulsion force was computed. The obtained results are supporting the ability of the IPD to generate propulsive force and linear motion.